2022
DOI: 10.1111/tid.13935
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to heterologous prime‐booster vaccination in heart transplant recipients aged 18–70 years primed with a viral vector SARS‐CoV‐2 vaccine

Abstract: Solid organ transplant recipients have demonstrated a blunted immune response to standard 2‐dose vaccination against SARS‐CoV‐2. This study sought to determine the humoral response to heterologous booster vaccination (viral vector vaccine dose 1 and 2 + mRNA booster). Heart transplant recipients, aged 18 to 70 years of age who initially received two doses of the viral vector ChAdOx1 nCoV‐19 vaccine followed by a BNT162b2 mRNA booster were recruited. A detectable antibody response in the absence of prior SARS‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A study in Thailand showed that KTRs who received two doses of this vaccine had a response rate of 33.33% [ 90 ]. A Mexican study of liver transplant recipients showed an antibody positivity of 89.2% with BNT162b2 (Pfizer-BioNTech), 60% with ChAdOx1 nCOV-19 (Oxford-AstraZeneca), 76.9% with CoronaVac (Sinovac, Life Sciences, Beijing, China), 55.6% Ad5-nCov (Cansino, Biologics, Tianjin, China), and 68.2% Gam-COVID-Vac (Sputnik V, Gamaleya National Centre of Epidemiology and Microbiology, Russia), but did not specify the dosing of each vaccine [ 91 ]. Another study of HTRs showed an antibody response in 37.5% of patients after two doses of ChAdOx1 and 56% after the third dose with BNT162b2 (Pfizer-BNT) [ 92 ].…”
Section: Vaccine Boostersmentioning
confidence: 99%
“…A study in Thailand showed that KTRs who received two doses of this vaccine had a response rate of 33.33% [ 90 ]. A Mexican study of liver transplant recipients showed an antibody positivity of 89.2% with BNT162b2 (Pfizer-BioNTech), 60% with ChAdOx1 nCOV-19 (Oxford-AstraZeneca), 76.9% with CoronaVac (Sinovac, Life Sciences, Beijing, China), 55.6% Ad5-nCov (Cansino, Biologics, Tianjin, China), and 68.2% Gam-COVID-Vac (Sputnik V, Gamaleya National Centre of Epidemiology and Microbiology, Russia), but did not specify the dosing of each vaccine [ 91 ]. Another study of HTRs showed an antibody response in 37.5% of patients after two doses of ChAdOx1 and 56% after the third dose with BNT162b2 (Pfizer-BNT) [ 92 ].…”
Section: Vaccine Boostersmentioning
confidence: 99%